Investigating fraud risks assessment practices in public sector audits / Mohamad Mahsun ... [et al.] - Mahsun, Mohamad; Mohamed, Nafsiah; Syed Yusuf, Sharifah Norzehan; Yuhertiana, Indrawati (Universiti Teknologi MARA, 2021)
Fraud Risk Assessment (FRA) is claimed to be an important activity at the audit planning stage in both the private and public sectors. In fact, because of the importance of FRA activities, Auditing Standards (SAS 99, ISA 240, ISSAI 1240) have required auditors to carry out FRAs at the audit planning stage. FRA is considered as the core activity of financial audit planning because of the impact of fraud on the sustainability of an entity, quality of life, and economic growth. This study aimed to determine the practice of FRA in public sector audits and to find out more about the obstacles faced by auditors during the audit process and to find out the causes of these obstacles by considering the approach to the Audit Standards used. This study found that auditors' performance can be determined based on their complete compliance with audit standards. We have encountered a serious problem that requires firm action from the government or a competent official, namely the auditor's willingness in preparing the Fraud Risk Assessment Matrix. In addition, we recommend the Audit Standards Board to adopt international public sector auditing standards and disseminate them through training for auditors, students, and professionals.